Keihäänheittäjän kovatehoisen heittoharjoituksen akuutit vaikutukset kyynärnivelen toimintakykyyn ja kyynärniveleen - Viitikko, Eero (2024)
The most common ligament injury among javelin throwers is the ulnar collateral ligament (UCL) injury of the elbow, which typically requires surgical intervention, careful rehabilitation, and an average absence from competitive sports for approximately 15 months. With each throw, the UCL’s ability to withstand valgus stress during the throwing motion is exceeded, necessitating strong support from muscles dynamically stabilizing the joint, including those pronating the forearm and flexing the wrist and fingers. The aim of this study was to investigate the acute effects of high-intensity javelin throwing training on the width of the ulnar joint space and maximal forearm muscle strength in javelin throwers. Additionally, the study aimed to examine the potential associations between changes in muscle strength and joint space width, as well as the Oxford Elbow Score (OES) functional questionnaire. The goal was to identify tools for athletes to monitor the readiness of forearm muscles to act as dynamic stabilizers of the joint space during training session. The study was conducted as a part of research collaboration between the Finnish Institute of High Performance Sport (KIHU) and the University of Jyväskylä.